Der Klang meines Selbst: Aussprache und Selbstkonstruktion von Fremdsprachenlernenden - Müller, Mareike; Schmenk, Barbara (Konzepte aus der Sprachlehrforschung – Impulse für die Praxis: Festschrift für Karin Kleppin)
Dieser Beitrag untersucht den Einfluss der Aussprache auf die Selbstkonstruktion von Lernenden und deren Bereitschaft, sich auf die zu erlernende Sprache und Kultur einzulassen. Im Gegensatz zu traditionellen Forschungsansätzen wird die Aussprache dabei als subjektiv bedeutsame Dimension im Sprachlernprozess konzipiert, die die Wahrnehmungen der Lernenden gegenüber sich selbst, anderen Sprechenden und dem gesamten Lernkontext stark mitprägt. Die Untersuchungen basieren auf den Narrationen zweier kanadischer Germanistikstudierender, die zwei Semester an deutschen Universitäten verbrachten. Der Selbstfindungs- und Lernprozess beider Studierender im fremden Umfeld wird dabei wesentlich durch ihre Selbstwahrnehmungen gelenkt, welche wiederum stark um das Thema Aussprache kreisen. Obwohl sich beide Lernende sehr unterschiedlich als Sprechende des Deutschen konstruieren, fixieren sie sich darauf, wie sie meinen zu klingen und folglich wahrgenommen zu werden. Dabei erweist sich vor allem das Konstrukt des Native Speaker als zentraler Vergleichspunkt, an dem sich die Lernenden messen und der somit als Basis für die Wertung des Auslandsaufenthalts und des eigenen Lernerfolgs dient. Durch die Analyse subjektiver Lernertheorien entwirft dieser Beitrag einen gänzlich neuen Rahmen für die Betrachtung von Aussprache im Sprachlernprozess, der über die rein phonetische Dimension hinausgeht und den Fokus auf die sozialpsychologischen Funktionen von Aussprache lenkt.

IRIS: A Robust Information System Against Insider DoS Attacks - Eikel, Martina; Scheideler, Christian (Transactions on Parallel Computing)
In this work, we present the first scalable distributed information system, that is, a system with low storage overhead, that is provably robust against denial-of-service (DoS) attacks by a current insider. We allow a current insider to have complete knowledge about the information system and to have the power to block any ϵ-fraction of its servers by a DoS attack, where ϵ can be chosen up to a constant. The task of the system is to serve any collection of lookup requests with at most one per nonblocked server in an efficient way despite this attack. Previously, scalable solutions were only known for DoS attacks of past insiders, where a past insider only has complete knowledge about some past time point t0 of the information system. Scheideler et al. [Awerbuch and Scheideler 2007; Baumgart et al. 2009] showed that in this case, it is possible to design an information system so that any information that was inserted or last updated after t0 is safe against a DoS attack. But their constructions would not work at all for a current insider. The key idea behind our IRIS system is to make extensive use of coding. More precisely, we present two alternative distributed coding strategies with an at most logarithmic storage overhead that can handle up to a constant fraction of blocked servers.

Incremental Inductive Verification of Parameterized Timed Systems - Isenberg, Tobias (Proceedings of the 15th International Conference on Application of Concurrency to System Design (ACSD))
We propose an incremental workflow for the verification of parameterized systems modeled as symmetric networks of timed automata. Starting with a small number of timed automata in the network, a safety property is verified using IC3, a state-of-the-art algorithm based on induction.The result of the verification, an inductive strengthening, is reused proposing a candidate inductive strengthening for a larger network.If the candidate is valid, our main theorem states that the safety property holds for all sizes of the network of timed automata. Otherwise the number of automata is increased and the next iteration is started with a new run of IC3.We propose and thoroughly examine optimizations to our workflow, e.g. Feedback mechanisms to speed up the run of IC3.

Die Steuerungsfunktion von zentralen Abiturprüfungen – Analysen und kontroverse Einschätzungen der Aufgabenschwierigkeit und mögliche Rückkopplungen auf den Unterricht - Kahnert, Julia; Eickelmann, Birgit; Lorenz, Ramona; Bos, Wilfried (Governance im Bildungswesen zwischen Steuerung, Koordination und Marktgeschehen)

Impulse für eine Schule der Zukunft – Zentrale Ergebnisse der internationalen Schulleistungsstudie ICILS 2013 - Eickelmann, Birgit; Gerick, Julia; Bos, Wilfried (Zeitschrift Schul-Management)

Vermittlung digitaler Kompetenzen als neues Handlungsfeld für Schulen und Schulleitungen. Zentrale Ergebnisse der internationalen Schulleistungsstudie ICILS 2013 - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Digitale Medien in der Schule)

Bildungsgerechtigkeit 4.0 - ICILS 2013: Grundlage für eine neue Debatte zur Bildungsgerechtigkeit - Eickelmann, Birgit

Lehrerprofessionalisierung und Fortbildungsaktivitäten im Kontext von Schulentwicklung mit neuen Technologien - Gerick, Julia; Eickelmann, Birgit (Journal für Schulentwicklung)

Preparing teachers for schooling in the digital age: A meta-perspective on existing strategies and future challenges - Erstad, Ola; Eickelmann, Birgit; Eichhorn, Koos (Education and Information Technologies)

Schulische Prädiktoren für die Nutzung neuer Technologien im Mathematikunterricht der Primarstufe und ihre Zusammenhänge mit Schülerkompetenzen - Eickelmann, Birgit; Gerick, Julia; Bos, Wilfried (IGLU & TIMSS. 10 Jahre international vergleichende Schulleistungsforschung in der Grundschule. Vertiefende Analysen zu IGLU und TIMSS 2001 bis 2011)

Wie geht es weiter? Zentrale Befunde der Studie ICILS 2013 und mögliche Handlungs- und Entwicklungsperspektiven für Einzelschulen - Eickelmann, Birgit; Bos, Wilfried; Gerick, Julia (SchulVerwaltung NRW)

Implementierung eines hybriden Verschlüsselungsverfahrens nach Cramer und Shoup - Kalde, Benedikt

Total digital? - Wie Jugendliche Kompetenzen im Umgang mit neuen Technologien erwerben. Dokumentation der Analysen des Vertiefungsmoduls zu ICILS 2013 - Eickelmann, Birgit; Bos, Wilfried; Vennemann, Mario

Tackling Educational Challenges in a Digitally Networked World - Lai, Kwok-Wing; Davis, Niki; Eickelmann, Birgit; Erstad, Ola; Fisser, Petra; Gibson, David C.; Khaddage, Ferial; Knezek, Gerald; Webb, Mary (KEYCIT 2014. Key Competencies in Informatics and ICT)

Singulärwertzerlegung für μ-ähnliche Bregman-Divergenzen - Strotmann, Daniela

HybridTE: Traffic Engineering for Very Low-Cost Software-Defined Data-Center Networks - Wette, Philip; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
The size of modern data centers is constantly increasing. As it is not economic to interconnect all machines in the data center using a full-bisection-bandwidth network, techniques have to be developed to increase the efficiency of data-center networks. The Software-Defined Network paradigm opened the door for centralized traffic engineering (TE) in such environments. Up to now, there were already a number of TE proposals for SDN-controlled data centers that all work very well. However, these techniques either use a high amount of flow table entries or a high flow installation rate that overwhelms available switching hardware, or they require custom or very expensive end-of-line equipment to be usable in practice. We present HybridTE, a TE technique that uses (uncertain) information about large flows. Using this extra information, our technique has very low hardware requirements while maintaining better performance than existing TE techniques. This enables us to build very low-cost, high performance data-center networks.

IT-Unterstützung in Emergency Management & Response - Erfurth, Christian; Pottebaum, Jens (45. Jahrestagung der Gesellschaft für Informatik, Informatik 2015, Informatik, Energie und Umwelt, 28. September - 2. Oktober 2015 in Cottbus, Deutschland)
Keywords: Ver{\

Towards Establishing Monotonic Searchability in Self-Stabilizing Data Structures - Scheideler, Christian; Setzer, Alexander; Strothmann, Thim Frederik (Proceedings of the 19th International Conference on Principles of Distributed Systems (OPODIS))
Distributed applications are commonly based on overlay networks interconnecting their sites so that they can exchange information. For these overlay networks to preserve their functionality, they should be able to recover from various problems like membership changes or faults. Various self-stabilizing overlay networks have already been proposed in recent years, which have the advantage of being able to recover from any illegal state, but none of these networks can give any guarantees on its functionality while the recovery process is going on. We initiate research on overlay networks that are not only self-stabilizing but that also ensure that searchability is maintained while the recovery process is going on, as long as there are no corrupted messages in the system. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We call this property monotonic searchability. We show that in general it is impossible to provide monotonic searchability if corrupted messages are present in the system, which justifies the restriction to system states without corrupted messages. Furthermore, we provide a self-stabilizing protocol for the line for which we can also show monotonic searchability. It turns out that even for the line it is non-trivial to achieve this property. Additionally, we extend our protocol to deal with node departures in terms of the Finite Departure Problem of Foreback et. al (SSS 2014). This makes our protocol even capable of handling node dynamics.

Towards a Universal Approach for the Finite Departure Problem in Overlay Networks - Koutsopoulos, Andreas; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 17th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. There are a number of studies for safe node exclusion if the overlay is in a well-defined state, but almost no formal results are known for the case in which the overlay network is in an arbitrary initial state, i.e., when looking for a self-stabilizing solution for excluding leaving nodes. We study this problem in two variants: the Finite Departure Problem (FDP) and the Finite Sleep Problem (FSP). In the FDP the leaving nodes have to irrevocably decide when it is safe to leave the network, whereas in the FSP, this leaving decision does not have to be final: the nodes may resume computation when woken up by an incoming message. We are the first to present a self-stabilizing protocol for the FDP and the FSP that can be combined with a large class of overlay maintenance protocols so that these are then guaranteed to safely exclude leaving nodes from the system from any initial state while operating as specified for the staying nodes. In order to formally define the properties these overlay maintenance protocols have to satisfy, we identify four basic primitives for manipulating edges in an overlay network that might be of independent interest.

The impact of communication patterns on distributed locally self-adjusting binary search trees - Strothmann, Thim Frederik (Proceedings of the 9th International Workshop on Algorithms and Computation (WALCOM))
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm, which is closely related to the nearly thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided.To do so, the process of self-adjustment is modeled similarly to a basic network creation game, in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and convergence is related to certain structures of the communication interests, which we call conflicts.We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well.Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.